A proposed vision to improve learning outcomes in the field of natural sciences in light of the reasons for the low results of national tests (Nafi) In the Kingdom of Saudi Arabia - Moalwi, Monahi Abdulrhman; Al-Shahrany, Abdullah Saeed; Al Orij, Ahmad Mohammad; Al-Khathami, Saad Mohammed; Mughbash, Abdullah Ali; Al-Shahrani, Mohammed Mufarrih (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to identify the underlying causes of low student performance in the national study aimassessment tests (NAFS) in the field of natural sciences, from the perspectives of both teachers and students. Additionally, it sought to propose a conceptual framework for improving learning outcomes in natural sciences based on these identified causes. The study employed a mixed-methods approach, utilizing two questionnaire instruments (teacher/student), each structured around eight dimensions, in addition to semi-structured interviews. The study sample consisted of 837 students and 238 science teachers affiliated with the General Directorate of Education in the Asir Region, all of whom were targeted by the NAFS assessments at the elementary and intermediate levels, The findings revealed that the role of school administration and students’ personal readiness were among the most significant contributing factors to the decline in students’ performance in the NAFS natural sciences test, according to the participants. In contrast, teaching strategies and family-related factors were perceived as the least contributing dimensions. Based on these results, a proposed framework was developed to enhance learning outcomes in natural sciences, incorporating targeted recommendations across four key domains: the school, the teacher, the student, and the family. In light of the findings, the study concludes with several recommendations, the most notable of which is encouraging schools participating in the NAFS assessments to adopt and benefit from the proposed framework to improve student outcomes.